ESG Disclosure and Tax Avoidance The Mediating Role of Financial Constraints (E-Jurnal Akuntansi, 2026)
The objective of this reserach is to determine the extent to which ESG disclosure affects tax avoidance, with a focus on how financial constraints mediate this relationship within Indonesian non-financial companies. The data were analyzed using Hayes PROCESS Model 4. ESG disclosure is found to be able to reduce tax avoidance actions, indicating that increased ESG disclosure is associated with greater corporate compliance. Interestingly, the results indicate that financial constraints do not serve as a mediating mechanism in this context. Rather, financial constraints independently correlate negatively with tax avoidance, implying that capital-constrained firms may shy away from aggressive tax strategies. Supplemental findings reveal that the social pillar is the primary catalyst behind the ESG-tax avoidance link. These results highlight the role of ESG disclosure as a transparency mechanism and the importance of disaggregated analysis in understanding corporate tax behavior.
Keywords: Tax Avoidance; ESG Disclosure; Financial Constraints